Flame Retardancy and Physical-mechanical Properties of Poplar Veneers Impregnated by Calcium Carbonate - Pingping Guo; Xiping Zhao; Xiaodong Zhu; Yu Liu; Qi Feng (BioResources, 2023)
Fast-growing poplar (Populus tomentosa Carr) can produce wood veneers, but their poor quality restricts their application in construction and building. Modification of wood has the potential to improve its properties. In this study, poplar veneers were impregnated with calcium carbonate (CaCO3) to reinforce their performance. The results showed that CaCO3 was uniformly distributed in cell lumens in impregnated veneers. After impregnation, the maximum weight gain rate was up to 41.4%, and water uptake decreased from 6.82% to 0.94%. The hardness increased from 7.6 to 10.0 MPa, and the extent of wear fell from 0.91% to 0.05%. The ignition time was prolonged, and the heat release rate and total heat release were low. Experimental results demonstrated that CaCO3 improved the physical-mechanical properties and flame retardancy of poplar veneers.